Judgment, Truth and Reality in F. H. Bradley. Trans/Form/Ação: Unesp Journal of Philosophy - Briceno-Dominguez, J (UNESP-MARILIA, 2024)
What does the truth of a judgment consist of, according to F. H. Bradley? What is its ultimate nature? In particular, how does such a property relate to reality? At least three interpretive theses have been offered: (i) that Bradley defended a theory of truth as coherence; (ii) that, rather, Bradley defended a robust variant of the identity theory of truth; and (iii) that, in any case, Bradley rejected the correspondence theory of truth. In this article I question these three theses and argue that the position defended by Bradley is perfectly compatible with a weak variant of the correspondence theory of truth. This, by the way, makes his position vulnerable to certain objections. Bradley s merit consists not so much in having answered them satisfactorily as in having anticipated them and assumed them as eventual consequences of his position.